THE EFFECT OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE AND TRUST ON INTENTION TO USE DANA AS A MOBILE PAYMENT - Cindy Lavenia Chikita Paramitha Mogot; David P. E. Saerang; Merinda H. C. Pandowo (Universitas Sam Ratulangi, 2023)
The development of technology causes rapid changes in the economic world. This includes fintech, where a combination between smartphones, applications, and the internet can be a digital mobile payment tool. This study aims to analyze the perceived usefulness, perceived ease of use and trust can influence the customer's intention to use Dana as their mobile payment. This study uses quantitative method. Questionnaire is used to collect the data. This research derived and examined the model through multiple linear regression model in a sample of 100 respondents who have made transaction using Dana in the last six months in Manado. Findings of this research show that perceived usefulness, perceived ease of use and trust simultaneously influence customer's intention to use Dana as their mobile payment. Recommendations for this research are Dana remains consistent and develops the application system, made interesting for its appearance, and can add 24-hour customer service live chat features so that users feel easy, helpful, and have more trust when making transactions using Dana. Keyword: perceived usefulness, perceived ease of use, trust, intention to use